Outcome of thoracic endovascular aortic repair in patients with thoracic and thoracoabdominal aortic aneurysms - Bischoff, Moritz; Ante, Marius; Meisenbacher, Katrin; Böckler, Dittmar (Journal of vascular surgery, 2016)
Objective - This study reports the long-term results after thoracic endovascular aortic repair (TEVAR) in thoracic aortic aneurysms (TAAs) and thoracoabdominal aortic aneurysms (TAAAs). - Methods - Between 1997 and 2010, 269 patients were treated with TEVAR, 100 of them (72 male; mean age, 68.3 years) for aneurysmal disease. An intact TAA (iTAA) was present in 49 patients and an intact TAAA (iTAAA) in 18. In 25 patients, there was a ruptured TAA or ruptured TAAA (rTAA). Eight patients were admitted with a post-traumatic TAA (pTAA). Retrospective analysis was performed from a prospectively maintained database. Primary end points were 5-year all-cause and TEVAR-related mortality. Secondary end points were causes of death, complications, and reinterventions (RIs). A 5-year follow-up was complete in all cases. - Results - The overall 5-year mortality rate was 50% (40.8% in iTAA, 80% in rTAA, 12.5% in pTAA, and 50% in iTAAA, respectively; log-rank test, P = .00012). The overall procedure-related mortality was 21% (10.2% [n = 5] in iTAA, 40% [n = 10] in rTAA, 33% [n = 6] in iTAAA, and 0 in pTAA, respectively; log-rank test, P = .00013). Freedom from complication was 52%, 47.2%, and 47.2% at 1, 3, and 5 years, respectively. There were a total of 30 RIs in 25 patients. Freedom from RI was 82%, 77.8%, and 71.2% at 1, 3, and 5 years. Stepwise forward logistic regression analysis revealed rTAA and occurrence of complications were risk factors for survival (odds ratios, 7.7 and 4.2, respectively). - Conclusions - Long-term results after TEVAR for aneurysmatic aortic disease demonstrate considerable overall and procedure-related mortality in both elective and urgent indications. Complications and RIs occur still as late events and emphasize the necessity for long-term follow-up.